Traveling to unify:: analysis of a railway study journey to Germany (TST. Transportes, Servicios y Telecomunicaciones, 2022)
This article studies the travel made, between April and May 1940, by a group of Spanish railway technicians to Germany, following the invitation of the German Ministry of Communications to learn about Germany’s network and organizational structure, the Deutsche Reichsbahn. To this end, we fundamentally relied on the memory of the expedition written by the Spanish group. The conclusions reached by the commission are analysed in this article, particularly the possible applications of the German practices to the Spanish railways.
Keywords: Study tours; railways; Spain; Germany